ChemInform Abstract: Iron/Acetic Acid Mediated Intermolecular Tandem C—C and C—N Bond Formation: An Easy Access to Acridinone and Quinoline Derivatives. Issue 11 (March 2015) - Rajawinslin, R. R.; Gawande, Sachin D.; Kavala, Veerababurao; Huang, Yi‐Hsiang; Kuo, Chun‐Wei; Kuo, Ting‐Shen; Chen, Mei‐Ling; He, Chiu‐Hui; Yao, Ching‐Fa
Abstract Various substituted acridinones, quinolines, and biologically active compounds are obtained by an one‐pot reductive cyclization protocol under mild reaction conditions.